2018
DOI: 10.1021/acssuschemeng.8b03824
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Aggregation-Induced Emission Gels Based on Pillar[5]arene for Ultrasensitive Detection and Separation of Multianalytes

Abstract: A novel supramolecular AIE (aggregationinduced emission) gel (PMDP-G) based on pillar [5]arene which could ultrasensitively detect and separate multianalytes was efficiently constructed. First, a novel supramolecular gelator, PM (host), and a functionalized pillar[5]arene, DP (guest), were successfully designed and synthesized. Then, host PM and guest DP could construct a stable supramolecular AIE gel, PMDP-G, via "exo-wall" π−π interactions and host−guest interactions in cyclohexanol solution. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 79 publications
0
24
1
Order By: Relevance
“…The multianalyte detection concept, which was first proposed by De Silva's group ( Magri et al., 2006 ; Schmittel and Shu, 2012 ; Chen et al., 2015 ; Magri, 2021 ), has become a hotspot in the field of sensors owing to its advantages of high efficiency, rapidity, simultaneous recognition and in-situ detection ( Xu et al., 2017 ; Park et al., 2018 ; Zhang et al., 2018 ; Chen et al., 2019a ; Zhao et al., 2021 ; Slenders et al., 2021 ; Huang et al., 2021b ; Nakamitsu et al., 2021 ). Multianalyte sensors were originally designed for multiple metal ions ( Magri et al., 2006 ), but these systems have subsequently been developed for multiple bioactive molecules ( Yin et al., 2018 ; Zhang et al, 2020b ; Thanzeel et al., 2020 ), bacteria ( Zheng et al., 2018 ), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The multianalyte detection concept, which was first proposed by De Silva's group ( Magri et al., 2006 ; Schmittel and Shu, 2012 ; Chen et al., 2015 ; Magri, 2021 ), has become a hotspot in the field of sensors owing to its advantages of high efficiency, rapidity, simultaneous recognition and in-situ detection ( Xu et al., 2017 ; Park et al., 2018 ; Zhang et al., 2018 ; Chen et al., 2019a ; Zhao et al., 2021 ; Slenders et al., 2021 ; Huang et al., 2021b ; Nakamitsu et al., 2021 ). Multianalyte sensors were originally designed for multiple metal ions ( Magri et al., 2006 ), but these systems have subsequently been developed for multiple bioactive molecules ( Yin et al., 2018 ; Zhang et al, 2020b ; Thanzeel et al., 2020 ), bacteria ( Zheng et al., 2018 ), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results demonstrated that 97.5% of Fe 3+ could be efficiently removed by OUG even from extremely dilute solutions, which indicated the excellent adsorption capacity of OUG towards Fe 3+ . 6,56,57,64 As shown in Fig. S6 (ESI †), adsorption tests of OUG toward Fe 3+ in the pH range from 4 to 10 showed that the adsorption of OUG toward Fe 3+ showed excellent stability at different pH conditions (in the range of 92.1-97.5%).…”
Section: Application In the Rapid Removal Of Fe 3+mentioning
confidence: 92%
“…4a), indicating that the OUG combined with Fe 3+ via cation-p interactions between the urethane groups and Fe 3+ . 56,61 As Fig. 4b 2.95 ppm), which indicated the cation-anion interactions between Fe 3+ and F À or HSO 4 À could release the p-electrons of urethane groups, thus recovering the fluorescence of OUG.…”
Section: Synthesis and Characterizationmentioning
confidence: 93%
See 1 more Smart Citation
“…Scientists have made great efforts to solve this problem by combining covalent bonded polymer with non-covalent interactions, including H-bond and coordination bond [ 16 , 17 , 18 ]. Among these various non-covalent interactions, host-guest chemistry, the central of supramolecular chemistry, has attracted tremendous attention, since it endows the system with reversible, tunable and dynamic properties [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, Suzuki and Takata reported the formation of tough films by evaporation of water from dispersions of elastomer microspheres crosslinked with rotaxane supramolecules, which contained crown ether [ 27 ].…”
Section: Introductionmentioning
confidence: 99%